Enriching the learning experience: use of scientific information resources and participation in scientific research in higher education: case of Faculty of humanities and social sciences Zagreb - Vrana, Radovan (Array, 2012)
The aim of this paper is to present results of the research among students at the Faculty of humanities and social sciences in Zagreb (FHSS) on two important topics: students' use of scientific information resources and their active participation in scientific research, both as part of their curricular activities. To find out more about these two topics, a research project was designed. The results confirmed regular use of printed and digital scientific information resources locally stored in library at the FHSS and off site as well as scientific information resources on the Internet. Students demonstrated their satisfaction with availability and quality of scientific information resources in library at the FHSS. Students’ participation in the second activity - scientific research – is less than satisfactory as well as their activity of publishing results of their research. Both activities are important as they prepare students for future work as well as for lifelong learning and students should be motivated to be more active in both areas.